Vulvar herpes zoster infection: a rare and challenging diagnosis. Issue 12 (31st December 2021) - Martins, Matilde Matos; Ferreira, Patrícia; Maciel, Raquel; Costa, Cristina
Abstract : A 26-year-old woman under immunosuppression with infliximab due to Crohn's disease was referred to the gynaecology emergency room with dispersed and coalescing vesicular lesions on the vulvar region extending to the right lower limb involving S2–S3 dermatome, associated with severe pain. Clinical history, physical examination and serological testing was consistent with herpes zoster infection. The patient was treated with valaciclovir for 14 days and cefradine for 7 days (due to the possibility of secondary bacterial infection). Significant symptomatic improvement was noted after 1 week. The 1-year follow-up was unremarkable. According to our knowledge and review of the literature, this is one of the few cases reported of vulvar herpes zoster, especially related to infliximab.